Diagnostic methods of cardiomyopathy in dogs - old and new perspectives and methods - Domanjko-Petrič, Aleksandra (Slovenian veterinary research, 2008)
Dilated cardiomyopathy (DCM) is an important cause of morbidity and mortality especially in large breed dogs. New diagnostic methods have been developed in the past few years to diagnose the disease early and improve chances of survival. Familial predisposition to DCM in some breeds opens possibilities ofthe early diagnosing by genetic testing and research has been done to find the causative molecular abnormalities. Doppler echocardiography and new sensitive methods like Tissue Doppler Imaging (TDI), a 24 to 48 hours electrocardiography (Holter monitoring), and cardiac biochemical markers such as atrial natriuretic peptide (ANP), B-type natriuretic peptide (BNP), and cardiac troponin I are -among others - the most promising methods in detectionof DCM.
Keywords: Cardiomyopathy, congestive; diagnostične metode; dobermani; Dogs; Echocardiography; Genetics; kardiomiopatije; kardiovaskularne bolezni; psi